Digital support systems A case study of Swedish county councils - SUNDBERG, MICHAEL (My University, 2017)
Digitalisation is one of society’s most powerful agency of change, and has already changed or will change every industry. Therefore, it is essential to create learning organisations that can adapt to the rapid development of digitalisation. Old business models will be erased by new digital solutions and may be an issue for organisations within the public sector. This is why E-government is in an expansive stage in Sweden, and also the reason why this report has digital support systems as topic. Digital support systems have the potential to increase efficiency and enhance openness and transparency. It could be a tool for change and control, and enhance coordination and collaboration between similar organisations in the public sector. But there is still uncertainty as to how to handle such systems and make them as useful and efficient as possible. The purpose of the research is to understand what role digital support systems have in Swedish county councils. The aim is to analyse the opportunities and challenges related to digital support systems, but also to analyse an already developed web-based management system called Program for technical standard (PTS). It is a qualitative research approach, and a case study has been presented on digital support systems in Swedish county councils, and eight semi-structured interviews have been performed. The empirical findings show that there is a lack of a structural process when working with digital support systems, which could be related to lack of experience and competence. This has led to short-term solutions and new digital systems are founded all the time. PTS has the potential to become a helping tool for this, but it seems be in an early phase and some have recently joined PTS and others have not had the time to implement it. Conclusions can be made that digital systems have a possibility to invent structured internal processes and make information available in a more efficient way within county councils. This will enhance collaboration with others and standard rooms can be used and shared in a common database. It is also vital to note that digital support systems must be easy to understand and easy to use, otherwise they will be ignored.
Keywords: Samhällsbyggnadsteknik; Civil Engineering